Effect of Weather Parameters on Biomass Production in Pigeonpea - Bishnoi, O P; Niwas, Ram; Taneja, K D; Rao, V U.M (Annals of Arid Zone, 2016)
An experiment was conducted for developing response functions between biomass production and growing degree days and evaporation in pigeonpea (Cajanus cajan L. Mill . sp.), cultivars H-80-110, UPAS-120 and Manak with four dates of sowing (5 and 20 June, 5 and 20 July) at Research Farm of Haryana Agricultural University, Hisar, during kharif seasons of 1987 and 1988. Simple linear, logarithmic, exponential and multiple linear response functions were studied. which are presented in the text. The regression model of the form y = a + b x + c xl (y - dry maller g plant-1 ; x - growing degree days and Xl - evaporation) was the most satisfactory and can be used for prediction of dry biomass.